Assessment of Epizootiological-Epidemiological Situation on Natural Focal Infections in Aleksandrovsk-Sakhalin Territory of the Sakhalin Region - E. I. Andaev; M. V. Chesnokova; T. I. Borisova; E. A. Vershinin; S. A. Tatarnikov; N. V. Breneva; A. V. Mazepa; R. V. Adel’Shin; S. E. Khudchenko; E. A. Sidorova; O. V. Mel’Nikova; Yu. N. Trushina; et al. (Problems of Particularly Dangerous Infections, 2014)
Objective of the work was to carry out complex assessment of the current state of epizootic activity and epidemiological significance of the infectious disease natural foci in the Aleksandrovsk-Sakhalin territory of the Sakhalin Region. Trapped were 56 samples of small mammals in July, 2010; collected were 180 specimens of taiga tick imago, caught were 1000 specimens of mosquitoes. 223 samples of blood sera were taken from residents of the region. All the field data were tested to detect specific antibodies, antigens and genetic material of agents. Based on the results of epizootiological investigations, serological and molecular-genetic assays, demonstrated was the occurence of natural foci of leptospirosis, tularemia, tick-borne encephalitis, borreliosis, rickettsiosis, human granulocytic anaplasmosis, human monocytic ehrlichiosis, West Nile fever, Inco fever, Batai and Geto fevers, as well as HFRS with varying degree of activity manifestation in the territory of the region. Isolated was tick-borne encephalitis virus from mosquitoes. Цель работы заключалась в комплексной оценке современного состояния эпизоотической активности и эпидемиологической значимости природных очагов возбудителей инфекционных болезней в Александровск-Сахалинском районе Сахалинской области. В июле 2010 г. на разных участках района отловлено 56 особей мелких млекопитающих, собрано 180 экземпляров имаго таежных клещей, отловлено 1000 экземпляров комаров. От жителей района собрано 223 образца сывороток крови. Весь полевой материал исследовали для выявления специфических антител, антигенов и генетического материала возбудителей. По результатам эпизоотологического обследования, серологических и молекулярно-генетических исследований показано, что на территории района имеются природные очаги лептоспирозов, туляремии, клещевого энцефалита (КЭ), иксодовых клещевых боррелиозов (ИКБ), клещевого риккетсиоза (КР), гранулоцитарного анаплазмоза человека (ГАЧ), моноцитарного эрлихиоза человека (МЭЧ), лихорадки Западного Нила (ЛЗН), Инко, Гета, Батаи, ...